2022
DOI: 10.1590/2447-536x.v28i2.2424
|View full text |Cite
|
Sign up to set email alerts
|

Total phenolics, flavonoids, antioxidant activity, and α-glucosidase inhibitory activity of ornamental pepper and several other lines

Abstract: Ornamental chili is a type of chili plant that favors the value of beauty but still has a spicy taste. It generally has a purple fruit color because they contain anthocyanins. The biochemical content in ornamental chili is believed to have benefits for human health. This study aims to identify several biochemical compounds in several genotypes of ornamental chili and pure lines. The study was conducted using the microplate method which was repeated three times. The research design used was a completely randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…α-glucosidase inhibition has an important role in helping patients with type 2 diabetes mellitus [17]. Interestingly, ornamental chilies in our previous study had relatively high levels of AGI compounds [9].…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…α-glucosidase inhibition has an important role in helping patients with type 2 diabetes mellitus [17]. Interestingly, ornamental chilies in our previous study had relatively high levels of AGI compounds [9].…”
Section: Introductionmentioning
confidence: 64%
“…All sample preparations use 70% ethanol on chilies previously made into powder [9,15]. Harvested ripe fresh chilies were baked in the oven for 48 h at 40 • C. After drying, they were crushed into powder using a blender of up to 10 mesh sizes.…”
Section: Biochemical Experimental 231 Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole plant part of the P. grandiflora was extracted as the test sample solution. The sample extraction was using the maceration method with slight modifications [23]. Beginning with weighing the fresh weight, then the three selected genotypes of P. grandiflora were dried using an oven until the water content reached less than 10%.…”
Section: Plant Materials Preparation and Extraction Methodsmentioning
confidence: 99%
“…Therefore, the biochemical compounds in their fruits are also important. Sahid et al (2022) conducted a study to identify these compounds in ornamental pepper genotypes and found high contents of alpha-glucosidase inhibitors (AGI), reaching up to 83.27%. They attributed the high inhibitory activity of alpha-glucosidase to the purple colour of the fruits, indicating their potential in the prevention and treatment of diabetes.…”
Section: Qualitative Descriptorsmentioning
confidence: 99%